Ghrelin and Leptin and Their Relations with Insulin Resistance in Diabetes Mellitus Type 2 Patients (Baghdad Science Journal, 2022)
Ghrelin and leptin are hunger hormones related to type 2 diabetes mellitus (T2DM), and the pathogenesis of T2DM is the abnormality in insulin secretion and insulin resistance (IR). The aim of this study is to evaluate ghrelin and leptin concentrations in blood and to specify the relationship of these hormones as dependent variables with some biochemical and clinical measurements in T2DM patients. In this study, forty one T2DM and forty three non-diabetes mellitus (non-DM) subjects, aged between 40-60 years and with normal weight, were enrolled. Fasting serum ghrelin and leptin were estimated by enzyme-linked immunosorbent assay (ELISA). In our results ghrelin was significantly increased, and leptin was significantly decreased, in T2DM patients compared with non-DM subjects. Ghrelin was positively correlated with the fasting blood glucose (FBG) and IR, but inversely related to the insulin sensitivity (IS). Leptin was negatively correlated with mean arterial pressure (MAP), FBG, glycated hemoglobin (HbA1c), IR, low-density lipoprotein cholesterol, nitric oxide (NO), and alanine aminotransferase (ALT), as well as showed a linear correlation with IS and a strong dependence on sex. The area under the curve (AUC) value shows ghrelin and leptin as biomarkers for T2DM. In conclusion ghrelin and leptin hormones have predictive ability to predict T2DM, as they are significantly associated with IR, IS, free radicals, and lipid profile.